Transcriptome and Cell Physiological Analyses in Different Rice Cultivars Provide New Insights Into Adaptive and Salinity Stress Responses - Formentin, Elide; Sudiro, Cristina; Perin, Giorgio; Riccadonna, Samantha; Barizza, Elisabetta; Baldoni, Elena; Lavezzo, Enrico; Stevanato, Piergiorgio; Sacchi, Gian Attilio; Fontana, Paolo; Toppo, Stefano; Morosinotto, Tomas; et al. (Frontiers in Plant Science, 2018)
Salinity tolerance is a trait investigated deeply in recent years for its agricultural importance. Several features as regulation of ionic transporters and metabolic adjustments have been identified as salt tolerance hallmarks. Nevertheless, due to the complexity of the trait, the results achieved so far have met with limited success in improving the salt tolerance of rice plants when tested in the field, suggesting that a deeper understanding of the tolerance mechanisms is still required. In this work, differences between two varieties of rice with contrasting salt sensitivity were unveiled by the imaging photosynthetic parameters, ion content analysis and a transcriptomic approach. The transcriptomic analysis conducted on tolerant plants supported the setting up of an adaptive program consisting of the sodium distribution preferentially limited to the roots and older leaves, and in the activation of regulatory mechanisms of photosynthesis in the new leaves. As a result, plants resumed growth even under prolonged saline stress. In contrast, in the sensitive variety, RNA-seq analysis revealed a misleading response, ending into senescence and cell death. The physiological response at the cellular level was investigated by measuring the intracellular profile of H2O2 in the roots, using a fluorescent probe. In the roots of tolerant plants, a quick response was observed with an increase in H2O2 production in 5 minutes after salt treatment. The expression analysis of some of the genes involved in perception, signal transduction and salt stress response confirmed their early induction in roots of tolerant plants compared to sensitive ones. By inhibiting the synthesis of the apoplastic H2O2, a reduction in the expression of these genes was detected. Our results indicate that a quick H2O2 signalling in the roots participates in a coordinated response that leads to adaptation instead of senescence in salt-treated rice plants.